Planck intermediate results LI. Features in the cosmic microwave background temperature power spectrum and shifts in cosmological parameters - Aghanim,N; Akrami,Y; Ashdown,M; Aumont,J; Baccigalupi,C; Ballardini,M; Banday,AJ; Barreiro,RB; Bartolo,N; Basak,S; Benabed,K; Bersanelli,M; et al. (Astronomy and Astrophysics, 2017)
The six parameters of the standard ΛCDM model have best-fit values derived from the Planck temperature power spectrum that are shiftedsomewhat from the best-fit values derived from WMAP data. These shifts are driven by features in the Planck temperature power spectrum atangular scales that had never before been measured to cosmic-variance level precision. We have investigated these shifts to determine whetherthey are within the range of expectation and to understand their origin in the data. Taking our parameter set to be the optical depth of the reionizedintergalactic medium τ, the baryon density ωb, the matter density ωm, the angular size of the sound horizon θ∗, the spectral index of the primordialpower spectrum, ns, and Ase−2τ(where Asis the amplitude of the primordial power spectrum), we have examined the change in best-fit valuesbetween a WMAP-like large angular-scale data set (with multipole moment ` < 800 in the Planck temperature power spectrum) and an all angularscaledata set (` < 2500 Planck temperature power spectrum), each with a prior on τ of 0.07 ± 0.02. We find that the shifts, in units of the 1σexpected dispersion for each parameter, are {τ, Ase−2τ, ns, ωm, ωb, θ∗} = {−1.7, −2.2, 1.2, −2.0, 1.1, 0.9}, with a χ2 value of 8.0. We findthat this χ2 value is exceeded in 15% of our simulated data sets, and that a parameter deviates by more than 2.2σ in 9% of simulated data sets,meaning that the shifts are not unusually large. Comparing ` < 800 instead to ` > 800, or splitting at a different multipole, yields similar results.We examined the ` < 800 model residuals in the ` > 800 power spectrum data and find that the features there that drive these shifts are a set ofoscillations across a broad range of angular scales. Although they partly appear similar to the effects of enhanced gravitational lensing